2020
DOI: 10.1186/s12913-020-05853-8
|View full text |Cite
|
Sign up to set email alerts
|

Otago exercise programme—from evidence to practice: a qualitative study of physiotherapists’ perceptions of the importance of organisational factors of leadership, context and culture for knowledge translation in Norway

Abstract: Background Falls and fall-related injuries are a major public health problem and an international priority for health services. Despite research showing that evidence-based fall prevention is effective, its translation into practice has been delayed and limited. Although organisational factors such as leadership, culture and context are key factors for implementing evidence-based practice, there is still limited information on whether these factors represent barriers in the Norwegian and international healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Data-extraction of descriptive data showed that in seven studies ( 38 40 , 43 , 46 , 48 , 49 ), only health care professionals (e.g., physical therapists, general practitioners, pharmacists, allied health assistances, occupational therapists) were included. In the other studies, there was a combination of health care and social care professionals (e.g., informal care, social service workers) ( 41 , 47 ) and/or other professionals (e.g., clinical support staff, fitness leaders, practice site leaders, volunteers) ( 42 , 44 , 45 , 50 52 ). Furthermore, eleven studies ( 38 40 , 42 45 , 48 50 , 52 ) focused primarily on primary care as setting; the other four studies ( 41 , 46 , 47 , 51 ) concentrated on a broader community-based setting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data-extraction of descriptive data showed that in seven studies ( 38 40 , 43 , 46 , 48 , 49 ), only health care professionals (e.g., physical therapists, general practitioners, pharmacists, allied health assistances, occupational therapists) were included. In the other studies, there was a combination of health care and social care professionals (e.g., informal care, social service workers) ( 41 , 47 ) and/or other professionals (e.g., clinical support staff, fitness leaders, practice site leaders, volunteers) ( 42 , 44 , 45 , 50 52 ). Furthermore, eleven studies ( 38 40 , 42 45 , 48 50 , 52 ) focused primarily on primary care as setting; the other four studies ( 41 , 46 , 47 , 51 ) concentrated on a broader community-based setting.…”
Section: Resultsmentioning
confidence: 99%
“…In the other studies, there was a combination of health care and social care professionals (e.g., informal care, social service workers) ( 41 , 47 ) and/or other professionals (e.g., clinical support staff, fitness leaders, practice site leaders, volunteers) ( 42 , 44 , 45 , 50 52 ). Furthermore, eleven studies ( 38 40 , 42 45 , 48 50 , 52 ) focused primarily on primary care as setting; the other four studies ( 41 , 46 , 47 , 51 ) concentrated on a broader community-based setting. Ten studies ( 39 41 , 44 49 , 52 ) used qualitative approaches only, such as semi-structured interviews and focus groups, whereas five studies ( 38 , 42 , 43 , 50 , 51 ) applied mixed methods with a qualitative and quantitative approach (e.g., surveys and documents).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding being involved in implementing the new vision assessment routines in the project, all the participants agreed it was important for them that their leader supported and facilitated their participation in this implementation project. A recent Norwegian study also highlights that an empowering leader is a facilitator for implementation in municipal health care services [ 55 ].…”
Section: Discussionmentioning
confidence: 99%